School choice, student sorting and academic performance - Andrei Munteanu (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2024)
This study examines the impact of school choice on academic achievement. I use differences in the number of schools across similar Romanian towns, generating variation in school choice for local students, who compete for seats via test scores. I find that more school choice results in increased sorting of students by admission scores across different schools. Sorting widens achievement gaps between high- and low-admission score students. High-scorers having access to better teachers and peer effects are the primary factors explaining these widening gaps. Lastly, between-school competition via school choice does not increase average achievement levels.
Keywords: I24; I21; I28; 330; education; school choice; sorting; inequality; peers; teachers